PERANCANGAN SISTEM INFORMASI BOOKING ONLINE PADA SALON NONI BEAUTY STUDIO - Luthfia Rohimah (SPEED - Sentra Penelitian Engineering dan Edukasi, 2021)
Salon NoniBeautyStudio is a salon that provides grooming services for women. This salon has a problem with waiting time in line and consuming a lot of time for customers. Responding to this problem, the NoniBeautyStudio salon needs to design an online appointment system, which can arrange the salon according to the scheduled time, thereby shortening the time for customers. One of the objectives of this research is to provide solutions to the problems mentioned above on a system that is still running manually by designing an online reservation system and using the prototype method. The results obtained are reflected in the system for making appointments, choosing treatments and paying online, and making the process easier, more effective and efficient. The design of information systems is the best solution to overcome the problems of Salon NoniBeautyStudio to achieve more effective activities. When designing an online ordering system, it is best to computerize the manual system so that you can connect to the mail server in the future, so that you can automatically receive order confirmations, which is more effective, easier and more convenient. soon.Keywords: Information System Design, Online Booking System, Salon